Preserving of intercostobrachial nerve relieves breast carcinoma patients from postmastectomy pain syndrome - Kumar, Girish N. M.; Chayampurath, Ramesan; Parambil, Sasi M. (International Journal of Research in Medical Sciences, 2017)
Background: Post-mastectomy pain syndrome (PMPS) is a complication experienced by majority of the patients who undergo breast surgery for cancer. The etiology of this chronic neuropathic pain syndrome seems to be complex and it is still understood below par. Injury to the intercostobrachial (ICB) nerve is presumed to be the dominant one for developing PMPS. This prospective study was designed to appraise the effect of preservation of intercostobrachial nerve on post-mastectomy pain syndrome and also to determine the most common anatomical variation of the intercostobrachial nerve during surgery. Methods: A total of 100 patients were included in this study and were divided into 2 groups. Group A included patients with ICB nerve preserved and Group B patients with ICB nerve sectioned. The patients were evaluated for pain subjectively on the 2nd day, 1 month and in the 3rd month post-operatively by short form of McGill pain questionnaire and visual analog scale. During surgical dissection, anatomical variation of ICB nerve was ascertained each time. Results: After 3 months, 68.2% of the patients were asymptomatic in Group A (ICB nerve preservation group) and 31.8% in the Group B (nerve section group) (chi-square test was applied and p value was 0.002). We found that type 1 anatomical variation was commonest with 87%. Conclusions: Preservation of ICB nerve might greatly decrease the incidence of PMPS. Hence, the insight of the anatomical variations of this nerve is very crucial for the operating surgeons to preserve them and to prevent PMPS.